2016
DOI: 10.1002/cb.1591
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of advertising appeals and their relationship to product attractiveness and buying intentions

Abstract: This study examines the effects of various visual apparel advertisements on consumers' brain activation during exposure to different types of advertising appeals (i.e., celebrity, non‐celebrity, and rational). The influence on consumer perceptions of products and their subsequent buying intentions are also measured. A repeated measures experimental design was employed, and the total of 27 right‐handed female subjects participated in the study. The results of the quantitative data showed significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…These results are similar to those achieved in recent studies where congruent (as opposed to incongruent) stimuli were shown [ 82 ], although they did not use food stimuli. Furthermore, our results are in line with Chang et al [ 83 ], who observed that SPL activity was detected by showing non-congruent (vs. famous) stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to those achieved in recent studies where congruent (as opposed to incongruent) stimuli were shown [ 82 ], although they did not use food stimuli. Furthermore, our results are in line with Chang et al [ 83 ], who observed that SPL activity was detected by showing non-congruent (vs. famous) stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…Spokespersons credibility positively impact the consumer's attitude towards advertisement, (Lee & Koo, 2016) and using a popular celebrity as an endorser could help to improve the subject rating of the commercial (Rashid, Nallamuthu, & Sidin, 2002). The appeal associated with the advertisements featuring celebrities leads to heightened brain activation of the memory-related region as reported in the fMRI study of celebrity advertisement by Chang, O'Boyle, Anderson, and Suttikun (2016). Celebrity endorsement not only results in positive advertisement ratings but also a better product evaluation (Cooper, 1984;Dean & Biswas, 2001).…”
Section: Celebrity Credibility and Advertisement Attitudementioning
confidence: 97%
“…Advertising appeals are used to attract the audience’s attention, as well as influence their attitudes and emotions regarding the product, service, or idea [ 17 , 29 ]. If an audience has a favorable feeling toward an advertisement, they are more likely to accept and even “enjoy” the ad message [ 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%